Designing Framework for Standardization Case Study: Lithium-Ion Battery Module in Electric Vehicle Application - Wahyudi Sutopo; Evizal Abdul Kadir (Institute of Advanced Engineering and Science, 2018)
Standardization is one of the important things before to deploy a product. Regulation such as national standard has important roles in industry. The roles of standard such as ensuring safety for consumer and producer, increasing product competitiveness, and reducing trade berries. Indonesia is currently in the stage of developing industry of electric vehicle, so that standard which is related to electric vehicle, one of it is standard for the electric vehicle battery. Besides that, Indonesia does not have a relevant standard to regulate. This study is intended to make a framework for standardization of lithium-ion battery module product using A Framework for Analysis, Comparison, and Testing of Standard (FACTS) approach. There are three stages in FACTS approach, they are analysis, comparison, and testing. Based on the result of this research, the framework of lithium-ion battery module product standard consists of 8 parameters.